Deteksi Risiko Pemanfaatan Wakaf Tunai Berbasis Wisata Religi Halal Perspektif SDGs di Madura - Dikuraisyin, Basar; najah , Ahmadun (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2025)
This research identifies, maps and mitigates risks in the utilisation of cash waqf for the development of halal religious tourism in Sumenep, Madura. The main problem of cash waqf management lies in the principle of waqf whose value should not decrease, but the benefits must be distributed. It is this principle that makes cash waqf managers (nadzir) must be careful in managing waqf funds with a scheme: minimising risk to the smallest point. This is where the significance of this research lies, waqf managers must be able to manage without reducing the value of waqf assets through risk detection. Risk detection is measured using the concept of maslahah which is tested through COSO Modification risk detection as a scientific measurement tool. The integration between these two instruments results in beneficial waqf management. This type of research is descriptive analytical with a phenomenological approach, looking at waqf instruments through the perspective of society. The data is taken from interviews with the waqf nadzir and some secondary data is taken from data on the website. The findings of this research show that risk detection of halal religious tourism cash waqf distribution, namely the entrepreneurial skills of nadzir and work partners with a score of 4.2. BMT Sumenep mitigates risks by forming a community that is symbiotic and expanding partners as guarantors of cash waqf assets. The implementation of cash waqf distribution is in accordance with the context of SDGs-1 and 8, reducing poverty and shaping human quality to ensure a decent life. Promoting the benefit of dururi to protect the family and social (hifd al-maal wa an-nasl).